The Effectiveness of Child-Centered Mindfulness Therapy on Social Anxiety and Bullying Among Aggressive Male Students - Azam Sobhani Najafabadi; Mahbobeh Sadat Fadavi; Ali Mahdad (مجله علوم پزشکی صدرا, 2024)
Introduction: Aggression in children and teenagers can lead to psychological and social harm to themselves and those around them. Given this, the present study aimed to examine the effect of child-centered mindfulness therapy on reducing social anxiety and bullying among aggressive male students.Methods: The research method employed in this study was quasi-experimental, with a pre-test, post-test, control group design, and a two-month follow-up period. The statistical population comprised aggressive students aged 9-12 years from the second elementary school in Isfahan City during the academic year of 2022-2023. A total of 36 aggressive male students were selected through purposive sampling and randomly assigned to experimental and control groups (18 students in each group). The experimental group underwent child-centered mindfulness therapy for ten weeks, with each session lasting 75 minutes. The Aggression Questionnaire (AQ), Social Anxiety Questionnaire (SAQ), and Bullying Questionnaire (BQ) were used in this research. The data were analyzed using mixed ANOVA and Bonferroni post hoc test via SPSS23 statistical software.Results: The results indicated that child-centered mindfulness therapy significantly affected social anxiety (F=54.37; eta=0.61; p<0.0001) and bullying (F=71.90; eta=0.68; p<0.0001) among aggressive male students.Conclusion: The findings of this research suggest that child-centered mindfulness therapy, which involves accepting feelings without judgment, conscious actions and thoughts, and focusing on the task at hand, can serve as an effective method to reduce social anxiety and bullying among aggressive male students.